Local biodiversity is higher inside than outside terrestrial protected areas worldwide - Claudia L. Gray (Nature Portfolio, 2016)
Protected areas are thought essential for biodiversity conservation, but few studies confirm that protection benefits species. Here, Gray and Hill et al. analyse a global, taxonomically broad database to show that local species richness and abundance are higher inside protected areas than outside.